FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA AKUNTANSI FE UST MENGIKUTI UJIAN SERTIFIKASI AKUNTAN PUBLIK (USAP) - Adia Adi Prabowo (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
Students who want to work as public accountants are required to first take the Public Accountants Certification Exam which is held by the Indonesian Institute of Certified Public Accountants, but students who take the public accountant certification exam are still minimal. The purpose of this study is to determine the effect of economic motivation, personality, barriers, social motivation and quality motivation on accounting students’ interest in taking the Public Accountant Certification Exam.The research respondents were all students of semester VI and above Accounting Study Program Department of Accounting SarjanawiyataTamansiswa University. The instrument testing was carried out using validity and reliability tests. To determine the accuracy of the model, classical assumption testing is carried out followed by multiple regression analysis both partially and simultaneously. The results of this study indicate that the variables of economic motivation, personality, exam barriers, social motivation and quality motivation simultaneously influence the interest of accounting students taking the Public Accountant Certification Exam by explaining the variation expressed in the coefficient of determination, showing that 66.6 percent of the variation in interest determined by social motivation and personality, while 33.4 percent is determined by other variables not examined in this study but partially personality and social motivation have a significant influence on the interests of accounting students taking the Public Accountant Certification Exam, while economic motivation variables, test barriers, and quality motivation does not have a significant influence on the interests of accounting students taking the Public Accountant Certification Exam.